2011
DOI: 10.1093/jxb/err408
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular analysis of starch metabolism in developing barley seeds using a non-aqueous fractionation method

Abstract: Compartmentation of metabolism in developing seeds is poorly understood due to the lack of data on metabolite distributions at the subcellular level. In this report, a non-aqueous fractionation method is described that allows subcellular concentrations of metabolites in developing barley endosperm to be calculated. (i) Analysis of subcellular volumes in developing endosperm using micrographs shows that plastids and cytosol occupy 50.5% and 49.9% of the total cell volume, respectively, while vacuoles and mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 64 publications
1
41
1
3
Order By: Relevance
“…These were then compared with their respective K eq (the ratio of product and reactant concentrations at which forward and reverse reaction rates are equal) to reveal how far each reaction was displaced from its chemical equilibrium (Table IV). Following Tiessen et al (2012), we considered a reaction as irreversible when the mass-action ratio is displaced from its K eq by a factor of more than 10. The outcomes indicated that both Suc cleavage mediated by Suc synthase and hexose mobilization mediated by glucokinases/fructokinases were essentially irreversible in vivo in the oilseed rape embryo (Table IV).…”
Section: The Initial and Final Steps Of Glycolysis Are Essentially Irmentioning
confidence: 99%
See 1 more Smart Citation
“…These were then compared with their respective K eq (the ratio of product and reactant concentrations at which forward and reverse reaction rates are equal) to reveal how far each reaction was displaced from its chemical equilibrium (Table IV). Following Tiessen et al (2012), we considered a reaction as irreversible when the mass-action ratio is displaced from its K eq by a factor of more than 10. The outcomes indicated that both Suc cleavage mediated by Suc synthase and hexose mobilization mediated by glucokinases/fructokinases were essentially irreversible in vivo in the oilseed rape embryo (Table IV).…”
Section: The Initial and Final Steps Of Glycolysis Are Essentially Irmentioning
confidence: 99%
“…7) of metabolic control of lipid/ starch partitioning in oilseeds has been established with only limited consideration of cellular compartmentation. Application of nonaqueous fractionation protocols would be needed to experimentally resolve metabolite compartmentation (Tiessen et al, 2012), but this technically challenging approach was not applicable. While we could not determine the distribution of metabolites among different subcellular compartments, for the interpretation of metabolite data in our study, it is of interest to know which of the measured metabolites are likely to be found predominantly in the metabolically highly active compartments (i.e.…”
Section: Complexity Of Subcellular Compartmentationmentioning
confidence: 99%
“…In contrast to chloroplasts, which produce ATP in the stroma, nonphotosynthetic plastids in endosperm import ATP from the cytosol, where its concentration is approximately 6-to 7-fold higher than in the organelle (Tiessen et al, 2012). Despite these considerations, cereals appear to have maintained selection not only for the cytosolic AGPase but also for the plastidial form(s) of the enzyme.…”
Section: Potential Metabolic Roles Of Plastidial Agpase In Endospermmentioning
confidence: 99%
“…the decrease in the starch deposition rate in maize endosperm at approximately 20 DAP; Prioul et al, 1994). The concentrations of the AGPase products and substrates in barley amyloplasts at mid development are such that the plastidial enzyme operates near equilibrium (Tiessen et al, 2012). Thus, plastidial AGPase potentially could respond to the metabolic environment so that, in some conditions, it catalyzes the reverse reaction and generates Glc-1-P from imported ADPGlc.…”
Section: Potential Metabolic Roles Of Plastidial Agpase In Endospermmentioning
confidence: 99%
“…31,32) During active photosynthesis, the levels of 3-PGA, GAP, G6P, R5P, and F6P are elevated in the plastid, while in the developing cereal endosperm, these metabolites together with F16BP, F26BP, and PEP, are expected to be present at significant levels due to the pronounced glycolysis that occurs in this tissue. [33][34][35][36] Thus the introduction of PLS-E38K, PLS-G101N, and PLS-E38K/G101N, which possess a broader range of activators, should result in enhanced starch production over that predicted based on increased sensitivity to 3-PGA alone.…”
Section: Activation Of Mutated Agpases By Various Sugar Metabolitesmentioning
confidence: 99%